Rawls and Religion - Bailey, Tom.; Gentile, Valentina (New York : Columbia University Press, 2015)
John Rawls's influential theory of justice and public reason has often been thought to exclude religion from politics, out of fear of its illiberal and destabilizing potentials. It has therefore been criticized by defenders of religion for marginalizing and alienating the wealth of religious sensibilities, voices, and demands now present in contemporary liberal societies. In this anthology, established scholars of Rawls and the philosophy of religion reexamine and rearticulate the central tenets of Rawls's theory to show they in fact offer sophisticated resources for accommodating and respond.
10. Islamic Politics and the Neutral State: A Friendly Amendment to Rawls?, by Abdullahi A. An-Na'imBibliography; List of Contributors; Index
Description based upon print version of record.
Keywords: Rawls, John, 1921-2002.; Religion; Rawls, John, -- 1921-2002.; Religion; RELIGION / Comparative Religion; RELIGION / Essays; RELIGION / Reference; Electronic books